INDIKATOR KINERJA DAERAH INDEKS PEMBANGUNAN MANUSIA KOTA MALANG - Rukayah (PANGRIPTA, 2019)
Human Development Index can be known with the Education Index indicator, Health Index, and Purchasing Power Index. Through this research it is hoped that information can be obtained related to Malang City development indicators specifically on the Human Development Index Indicator. The Human Development Index can be predicted using the Time Series Regression Method (Hildreth-Lu). Based on research that has been done the Malang City Human Development Index has been included very high category.